Clinical characterization and risk factors of Clostridium difficile infection in elderly patients in a Chinese hospital - Zhang Lihua; Dong Danfeng; Jiang Cen; Wang Xuefeng; Peng Yibing (Journal of Infection in Developing Countries)
Introduction: Clostridium difficile is a common cause of nosocomial diarrhea, especially in elderly patients. This study aimed to analyze the clinical features and assess the risk factors associated with Clostridium difficile infection (CDI) in elderly hospitalized patients. Methodology: A retrospective case-control study was conducted among elderly hospitalized patients (> 60 years of age) in a Chinese tertiary hospital between 2010 and 2013. Fifty-two CDI patients and 150 randomly selected non-CDI patients were included in the study. Clinical features of CDI and non-CDI patients were compared by appropriate statistical tests. Logistic regression analyses were performed on a series of factors to determine the risk factors for CDI among the elderly hospitalized patients. Results: The elderly CDI patients showed higher leukocyte counts, lower serum albumin levels, longer duration of hospital stay, and higher mortality compared to the non-CDI patients. The proportion of patients admitted to the intensive care unit or exposed to gastric acid suppressants was also significantly different (p < 0.05) between the two groups. Multivariate analysis indicated that serum creatinine (OR 1.004; 95% CI 1.001–1.008), surgical intervention (OR 6.132; 95% CI 2.594–14.493), the number of comorbidities (OR 2.573; 95% CI 1.353–4.892), gastrointestinal disease (OR 4.670; 95% CI 2.002–10.895), and antibiotic use (OR 6.718; 95% CI 2.846–15.859) were independently associated with CDI. Conclusions: This study revealed several risk factors for CDI among elderly hospitalized patients. These findings will increase the knowledge concerning this disease and provide information regarding the control and prevention of CDI in the elderly.